2010
DOI: 10.3109/0284186x.2010.498437
|View full text |Cite
|
Sign up to set email alerts
|

Variability of textural features in FDG PET images due to different acquisition modes and reconstruction parameters

Abstract: Background Characterization of textural features (spatial distributions of image intensity levels) has been considered as a tool for automatic tumor segmentation. The purpose of this work is to study the variability of the textural features in PET images due to different acquisition modes and reconstruction parameters. Material and methods Twenty patients with solid tumors underwent PET/CT scans on a GE Discovery VCT scanner, 45–60 minutes post-injection of 10 mCi of [18F]FDG. Scans were acquired in both 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
302
3
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(319 citation statements)
references
References 19 publications
(27 reference statements)
6
302
3
5
Order By: Relevance
“…We based this approach on methods reported in several clinical studies 41, 53, 54, 55. Also, Galavis et al36 used a similar scale to categorize the features based on their variation, and Tixier et al37 indicated that such limits were referenced to previously defined reproducibility limits for standard uptake values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We based this approach on methods reported in several clinical studies 41, 53, 54, 55. Also, Galavis et al36 used a similar scale to categorize the features based on their variation, and Tixier et al37 indicated that such limits were referenced to previously defined reproducibility limits for standard uptake values.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, varying reconstruction methods have evolved into sophisticated algorithms with various image qualities due to modern computing. A study by Galavis et al36 showed that different acquisition modes and image reconstruction settings might cause variation in radiomic features. Similarly, the gray‐level discretization of PET/CT images has shown to have a great impact on some radiomic features 37…”
Section: Introductionmentioning
confidence: 99%
“…Automated drawing ROI methods may reduce intra-and inter-observer variation. Likewise, Galavis et al [28] reported that some texture parameters exhibited large variations when PET images are acquired and processed with different modes. We included PET scans acquired on a single PET/CT system not to make factors of feature variability.…”
Section: Patientsmentioning
confidence: 99%
“…On the one hand, intra-tumour uptake heterogeneity was quantified considering only those indices that have been previously shown as robust considering image reconstruction and acquisition variability [23], and physiological reproducibility based on double baseline PET acquisitions [24]. Figure 1 illustrates the two types of heterogeneity parameters under consideration.…”
Section: Intra-tumour Heterogeneity Parametersmentioning
confidence: 99%
“…However, recent studies have shown that only a limited number of these TF derived indices are robust with respect to the clinical range of image reconstruction algorithms and acquisitions protocols [23], and reproducible with respect to physiological variability assessed on double baseline FDG PET scans [24]. Within the same context it has also been hypothesized that heterogeneity quantification could be dependent on the necessary functional tumour volume delineation method used, as well as be compromised by the low PET image spatial resolution and associated partial volume effects (PVE) [18,22], although this has never been thoroughly investigated.…”
mentioning
confidence: 99%